Pirates - Fox, E. T. (Dorling Kindersley Limited London, 2017)
DKfindout! Pirates takes kids back in time to discover the truth behind the myth. With beautiful photography, lively illustrations, and key curriculum information, the DKfindout! series will satisfy any child who is eager to learn and acquire facts and keep them coming back for more! For any kid that can't get enough of pirate facts, DKfindout! Pirates is packed with information, quizzes, fun facts and incredible images of every aspect of pirate life. Discover what pirates ate, what life was like onboard a ship, and the rules by which they led by. Immerse yourself in pirates with DKfindout!